2016
DOI: 10.1038/pr.2016.264
|View full text |Cite
|
Sign up to set email alerts
|

Sodium supply influences plasma sodium concentration and the risks of hyper- and hyponatremia in extremely preterm infants

Abstract: The supply of sodium, rather than fluid volume, is the major factor determining P-Na concentrations and the risks of hyper- and hyponatremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…Our study shows a linear relationship between peak sodium and GA in patients born between 24 and < 31 weeks. This extends previous results, showing a similar relationship in patients < 27 weeks GA [22], to a wider range of GA. The physiological mechanisms leading to the observed increase in sodium during the first days of life are most likely based on the postnatal changes of body composition, which occurs due to a significant reduction in extracellular water and reduction of total body water caused by pulmonary and transepidermal insensible water loss.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study shows a linear relationship between peak sodium and GA in patients born between 24 and < 31 weeks. This extends previous results, showing a similar relationship in patients < 27 weeks GA [22], to a wider range of GA. The physiological mechanisms leading to the observed increase in sodium during the first days of life are most likely based on the postnatal changes of body composition, which occurs due to a significant reduction in extracellular water and reduction of total body water caused by pulmonary and transepidermal insensible water loss.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is important to identify patients at risk and to monitor sodium closely in these patients. Since hypernatremia is either caused by an excess of sodium or by lack of body water, these parameters can be targeted easily by either reducing sodium administration [22], by increasing free body water [5] or by decreasing insensible water loss [7]. In adults it has been shown that targeting sodium and aiming at normal sodium levels leads to decreased morbidity and mortality [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Späth et al presented a postnatal weight change of −10 ± 7% (range −31% to +13%) in a cohort of 592 extremely low birthweight infants, with a nadir at a postnatal age of 4 days. They found that the average daily fluid intake on days 0‐3 after birth correlated positively with the percentage weight change from birth to day four of life . It has been proposed that, in addition to the contraction of extracellular fluid, up to half of the initial postnatal weight loss in low birthweight infants might represent failure to accrete or actual loss of lean mass and, or, fat .…”
Section: Discussionmentioning
confidence: 99%
“…After the catheter occluded on day 8, we assessed his blood pressure mainly by physical examination. The target ranges of osmotic agents were set with reference to previous studies, and his albumin level was kept above 2.5 g/dL to maintain osmotic pressure (24)(25)(26)(27). Echocardiography was performed to diagnose patent ductus arteriosus (PDA) on day 1.…”
Section: Case Descriptionmentioning
confidence: 99%